Impact of albumin infusion on prognosis in ICU patients with cirrhosis and AKI: insights from the MIMIC-IV database - Li, Mengqi; Ge, Yidi; Wang, Jingjing; Chen, Wenya; Li, Jiashuo; Deng, You; Xie, Wen (Frontiers in Pharmacology, 2024)
Abstract Background: Acute kidney injury (AKI) is common in cirrhotic patients, especially in the intensive care unit (ICU), and is often associated with poor prognosis. Albumin is often used for plasma volume expansion, but its efficacy in cirrhotic patients with AKI (excluding hepatorenal syndrome [HRS]) is debated. This study aimed to assess the impact of albumin therapy on prognosis in ICU patients with cirrhosis and non-HRS AKI. Methods: A retrospective analysis was conducted using the MIMIC-IV 2.2 database. The primary endpoint was 28-day mortality. Inverse probability of treatment weighting (IPTW) was used to balance baseline characteristics between the albumin and non-albumin groups. Results: A total of 1623 patients were included, with 586 receiving albumin. After IPTW, the sample sizes were 1713 in the non-albumin group and 1490 in the albumin group. Albumin administration was associated with higher rates of AKI recovery at 48 hours but did not improve 28-day mortality in the overall cohort. Further analysis revealed that using 5% albumin concentration was associated with improved 28-day mortality (HR 0.68; 95% CI 0.49-0.95; p = 0.025), whereas 25% albumin did not show benefit. In patients with high bilirubin levels, albumin treatment significantly reduced 28-day mortality. However, albumin therapy may increase 28-day mortality in certain subgroups, including patients with chronic kidney disease and baseline albumin levels > 3.3 g/dL. Conclusions: Although albumin therapy improved 28-day mortality in some cases, it may also increase mortality in certain subgroups.The use of albumin in critically ill patients with cirrhosis and AKI should be approached with greater consideration of its risks and benefits.